The Influence of Organizational Citizenship Behavior on Employee Performance Through Job Satisfaction in PVC Production - Ricky Lukito; Zeplin Jiwa Husada Tarigan; Maria Natalia Damayanti Maer (Universitas Kristen Petra dan Ikatan Sarjana Ekonomi Indonesia Cabang Surabaya, 2026)
This study aims to analyze the influence of Organizational Citizenship Behavior (OCB) on employee performance through job satisfaction in the PVC production department. The study used a quantitative, saturated sampling approach, so the entire population of 34 people was used as the sample. Primary data were collected through questionnaires and analyzed using Partial Least Squares (PLS). The results of the outer model evaluation showed that all indicators met the validity and reliability criteria. The results of the inner model showed R-square values of 0.587 for job satisfaction and 0.451 for employee performance, with a Q² value of 0.7733, indicating good predictive relevance. The results of the hypothesis test showed that OCB did not have a significant direct effect on employee performance. However, OCB had a positive and significant effect on job satisfaction, and job satisfaction had a positive and significant effect on employee performance. Job satisfaction was proven to mediate the effect of OCB on employee performance. These findings indicate that increasing OCB behavior does not necessarily directly improve performance, but can indirectly enhance performance by increasing employee job satisfaction.